Effect of Microbial Antagonists on the Development Of Bacterial Wilt on Tomato - Choo, Ee Fong (2003)
Bacterial wilt caused by Ralstonia solanacearum is the major constraint to the production of tomato in Malaysia. In this study, the effect of application methods of biological control agents to control bacterial wilt of MT11, a moderately resistant variety of tomato was evaluated under greenhouse and field condition. Six antagonistic strains of Pseudomonas aeruginosa showed in vitro antagonism towards R. solanacearum. Seed biopriming with these strains of P. aeruginosa either individually or in combination increased the percentage of seed germination. Whereas, biomass of plants was increased only after seeds were bio-primed with the combined strain. Combination of strains KT8+ 72PTT was used as seeds bioprime agent in greenhouse and field experiments. Penicillium sp. showed in vitro antagonism towards R. solanacearum Greenhouse experiment also showed that the antagonist could reduce the incidence of bacterial wilt on MT11. An experiment was carried out on the effect of the application methods and levels of concentration of the antagonist on the biomass of plants. Results showed that soil incorporated with Penicillium sp. just before transplanting Significantly reduced the biomass of top part of six true leaves seedlings. Direct drenching of antagonist also Significantly reduced the biomass of four-week-old seedlings, either at high or low concentration. However, no Significant reduction was observed in the biomass of root system and dry weight of top when the antagonist was incorporated into soil one week prior to transplanting. Two greenhouse trials were conducted to evaluate the integrated control using combination of bacterial and fungal antagonist and calcium nitrate, on MT11. Both the experiments showed reduced incidence of bacterial wilt on plants, which were treated with the integrated control measures. Combined treatment of seed bio-priming and carrier application of Penicillium sp. at high concentration recorded the lowest Disease Severity Index of bacterial wilt in the second greenhouse trial. Carrier application of Penicillium sp. provided better protection to plants compared to direct drenching regardless of inoculum concentration.